G554 Intra- and inter-observer variability in PDA size measured on transthoracic echocardiography (TTE) in extremely preterm babies. (25th October 2020) - Babla, K; Dumitru, R; Duffy, D; Richards, J; Kulkarni, A
Abstract : Background: The internal diameter of the patent ductus arteriosus (PDA) measured on transthoracic echocardiography (TTE) is commonly used in determining the need for treatment in clinical practice and enrolment in research trials. PDA size measured on TTE has not been well validated. Objective: To assess the intra- and inter-observer variability in PDA internal diameter measured on TTE on the same examination in babies born at ≤30 weeks' gestation admitted to St George's neonatal unit. Methods: We included 56 babies born ≤30 weeks' gestation that had a clinically indicated TTE. TTEs were performed by a single consultant neonatologist (AK) certified in echocardiography. PDAs were visualised using a high parasternal view, and cineloops were stored on DICOM Radiology viewing software without measurement annotations. PDAs were measured at the narrowest diameter on 2-Dimensional (2D) and Colour Doppler echocardiography assessment. A second certified consultant (DD) measured the internal diameter of PDA on the same 2D and colour echocardiography cineloops. They were blinded to each other's measurements. AK repeated measurements at a later date, blinded to his original measurements. Results: (Table 1 ) Bland-Altman Analysis examining PDA internal diameter measurements by two operators on the same cineloop. Intra-observer analysis showed an r 2 correlation coefficient of 0.68 (2D) and 0.53 (Colour). Comparison of all measurements showed Colour measurements a mean of 0.29 mm higher than 2D. Conclusion: The poor repeatability coefficients and repeatability indices, lead us to conclude that there is significant inter- and intra-observer variability in 2D and Colour echocardiography measurements of PDA diameter, even on the same cineloops. Thresholds and timing of treatment for PDA remain controversial. We advise caution when using diameter as surrogate marker for degree of shunting.